The Promoting integrity in the civil service: economic, legal and social aspects in the context of the republic of Kazakhstan - A. Talgatuly; G.A. Junusbekova; А.А. Tynyshbayeva (Хабаршысы. Экономика сериясы)
This article examines the concept of integrity in the civil service, its significance, and approaches to its development, with a particular emphasis on the economic dimensions and the impact of integrity on the efficiency of public administration. Theoretical foundations for strengthening the principle of integrity in the civil service are analyzed, with a focus on mechanisms for its institutionalization within the public governance system of the Republic of Kazakhstan.